Students' creative thinking ability assisted augmented reality based on visualizer-verbalizer cognitive style - Ayu Faradillah; Annisa Maulida (Universitas Hamzanwadi, 2022)
Creativity is the highest order of thinking, which leads students to generate new ways to find a solution to many unpredictable problems in the future. Although there are many studies on creative thinking ability, no research focused on augmented reality and visualizer-verbalizer cognitive style in creative thinking ability. This study aims to describe creative thinking ability assisted with augmented reality view from visualizer-verbalizer cognitive style. This study used a qualitative descriptive approach. The subjects of this study were selected four students' 52 from the 10th grade. The process of selecting this subject was analyzed by the Rasch Model analysis using Winsteps software version 3.73. The data were collected using Visualizer-Verbalizer Questionnaire (VVQ), a creative thinking ability test assisted with augmented reality and interview. The final scale from the visualizer scale has a Cronbach alpha value of 0.67, while the verbalizer scale has a Cronbach alpha value of 0.66. The results show that the visualizer students meet all the indicators of creative thinking ability: fluency, flexibility, originality, and elaboration. While the verbalizer students only meet fluency indicators or fluency and originality indicators in creative thinking ability. Therefore, based on this research analysis, teachers can pay more attention to the students' cognitive style in creative thinking ability.